2022
DOI: 10.3389/fonc.2021.802205
|View full text |Cite
|
Sign up to set email alerts
|

A Transfer Learning Radiomics Nomogram for Preoperative Prediction of Borrmann Type IV Gastric Cancer From Primary Gastric Lymphoma

Abstract: ObjectiveThis study aims to differentiate preoperative Borrmann type IV gastric cancer (GC) from primary gastric lymphoma (PGL) by transfer learning radiomics nomogram (TLRN) with whole slide images of GC as source domain data.Materials and MethodsThis study retrospectively enrolled 438 patients with histopathologic diagnoses of Borrmann type IV GC and PGL. They received CT examinations from three hospitals. Quantitative transfer learning features were extracted by the proposed transfer learning radiopathomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…To verify the superiority of the proposed AMSF-L1ELM, several state-of-the-art methods are used for comparison in two validation cohorts. Representative methods include the classic radiomics signature (RS) (Feng et al, 2021) based on radiomics features, a clinical model (CM) based on subjective signs and clinical information (Feng et al, 2021) From these results in Table 2, we can obtain the following insightful observations.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the superiority of the proposed AMSF-L1ELM, several state-of-the-art methods are used for comparison in two validation cohorts. Representative methods include the classic radiomics signature (RS) (Feng et al, 2021) based on radiomics features, a clinical model (CM) based on subjective signs and clinical information (Feng et al, 2021) From these results in Table 2, we can obtain the following insightful observations.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
“…Considering clinical practice, doctors often need to use a variety of means for disease diagnosis, such as lesion screening based on multisequence CT images (such as arterial phase and venous phase) and then pathological diagnosis based on WSI images. Additionally, the effectiveness of the transfer learning model, which was based on single-source domain WSI of gastric tissue and WSI of lung tissue, was preliminarily validated according to our previous work ( Feng et al, 2021 ). Considering the above observations, this manuscript plans to select the gastric WSIs (source domain 1), lung WSIs (source domain 2) and arterial phase CT images of gastric cancer (source domain 3) as the source domain data, and proposes a multisource transfer learning feature extraction network, as shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…However, acquiring a large number of medical images is difficult ( 20 ). Due to a pre-trained CNN known as “transfer learning (TL)” can be used to minimize overfitting with a small training size, TL has gradually been used in various medical image analysis domains in recent years ( 21 , 22 ). TL increases model performance in target tasks by transferring previously learned features from source tasks.…”
Section: Introductionmentioning
confidence: 99%
“…TL increases model performance in target tasks by transferring previously learned features from source tasks. A previous study found that a TL radiomics nomogram based on gastric whole slide images can assist in distinguishing primary gastric lymphoma from Borrmann type IV GC ( 22 ). In addition, Linlin et al ( 21 ) developed a convenient model based on deep learning-based radiomics characteristics to differentiate brain abscess from cystic glioma.…”
Section: Introductionmentioning
confidence: 99%
“…However, the size of datasets in the medical field is often small, and CNN is prone to over-fitting under the condition of small samples. To improve the effect of CNN under small samples, scholars have introduced transfer learning into CNN ( Tan et al, 2018 ; Feng et al, 2021 ). By imitating the mechanism of drawing inferences about other cases from one instance of the human brain, transfer learning uses the knowledge learned from a large source domain data to help the learning of the target task.…”
Section: Introductionmentioning
confidence: 99%